QUALITY OF EDUCATION SERVICES AND THEIR EFFECT ON STUDENT SATISFACTION: SURVEY AT VOCATIONAL ACADEMY IN BANDUNG CITY - Yunaningsih, Ani; Surahman, Fathur Darajat; Budiana, Deni; Septiawan, Fajar Eryanto (LPPM STIE Muhammadiah Bandung, 2022)
It is critical to offer excellent education services in light of universities' critical role in creating graduates who are knowledgeable and capable of competing in the global age. The following step will be influenced by whether you are unsatisfied, satisfied, or very pleased. Students that are pleased with the educational services they have gotten will spread the word. The goal of this research was to see how much of an impact educational service quality had on student happiness. This research used a quantitative technique with verification analysis. This research is confirmatory since it examines the hypothesis to make inductive or general choices. This research employs a questionnaire as a data gathering method. The author utilized Slovin to determine the number of samples used in this research since it is known that the population has more than 100 respondents. Path analysis is used in this study. Student happiness is influenced in part by the quality of educational services. This demonstrates that if the Quality of Education Services is correctly developed and maintained, Bandung City Vocational Academy students would be happy and favorably react to the campus.